ORF17 from the clavulanic acid biosynthesis gene cluster catalyzes the ATP-dependent formation of N-glycyl-clavaminic acid. - Arulanantham, H; Kershaw, N; Hewitson, K; Hughes, C; Thirkettle, J; Schofield, C (2006)
(3R,5R)-Clavulanic acid, a clinically used inhibitor of serine beta-lactamases, is produced by fermentation of Streptomyces clavuligerus. The early steps in clavulanic acid biosynthesis leading to the bicyclic beta-lactam intermediate (3S,5S)-clavaminic acid have been defined. However, the mechanism by which (3S,5S)-clavaminic acid is converted to the penultimate intermediate (3R,5R)-clavaldehyde is unclear. Disruption of orf15 or orf16, of the clavulanic acid biosynthesis gene cluster, blocks clavulanic acid production and leads to the accumulation of N-acetyl-glycyl-clavaminic acid and N-glycyl-clavaminic acid, suggesting that these compounds are intermediates in the pathway. Two alternative start codons have been proposed for orf17 to encode for two possible polypeptides, one of which has 92 N-terminal residues less then the other. The shorter version of orf17 was successfully expressed in Escherichia coli and purified as a monomeric protein. Sequence analyses predicting the ORF17 protein to be a member of the ATP-grasp fold superfamily were supported by soft ionization mass spectrometric analyses that demonstrated binding of ATP to the ORF17 protein. Semisynthetic clavaminic acid, prepared by in vitro reconstitution of the biosynthetic pathway from the synthetically accessible intermediate proclavaminic acid, was shown by mass spectrometric analyses to be converted to N-glycyl-clavaminic acid in the presence of ORF17, ATP, and glycine. Under the same conditions N-acetyl-glycine and clavaminic acid were not converted to N-acetyl-glycyl-clavaminic acid. The specificity of ORF17 as an N-glycyl-clavaminic acid synthetase, together with the reported accumulation of N-glycyl-clavaminic acid in orf15 and orf16 disruption mutants, suggested that N-glycyl-clavaminic acid is an intermediate in clavulanic acid biosynthesis.